2020
DOI: 10.3390/rel11020075
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Religiousness and Hope: Examining the Roles of Spirituality and Social Connections among Salvadoran Youth

Abstract: Given the strong link between religiousness and hope, we sought to further understand the relations of these potentially powerful resources for youth living in adversity. Although existing research suggests that religiousness might be associated with adolescent hope via spirituality and social connections, few studies have tested models that integrate both. Thus, as applied psychologists, the aim of this paper was to test a theoretical model in the lives of youth. Drawing on a Relational Developmental Systems … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 77 publications
1
13
0
2
Order By: Relevance
“…In the first tier, having a close relationship with a divine being may benefit parents' well-being by providing a stable source of strength, comfort, and hope. This assertion is supported by studies that find a positive associations between religious participation, spiritual beliefs, and hope (Ciarrocchi et al, 2008;King et al, 2020). In the second tier, having a spiritual view of family relationships may help in maintaining the quality of marital and parent-child relationships.…”
Section: Theoretical Frameworkmentioning
confidence: 87%
See 1 more Smart Citation
“…In the first tier, having a close relationship with a divine being may benefit parents' well-being by providing a stable source of strength, comfort, and hope. This assertion is supported by studies that find a positive associations between religious participation, spiritual beliefs, and hope (Ciarrocchi et al, 2008;King et al, 2020). In the second tier, having a spiritual view of family relationships may help in maintaining the quality of marital and parent-child relationships.…”
Section: Theoretical Frameworkmentioning
confidence: 87%
“…One indicator of well-being is hope, described as a positive motivational state that involves being confident in the ability to meet one's goals and finding ways to do so (Snyder et al, 1996). A study with Salvadoran youth found that the higher levels of religiosity were associated with higher levels of individual spirituality which, in turn, were related to greater hope (King et al, 2020). In this study, religiosity was described as religious participation and perceived importance of religion, whereas spirituality was measured using items referring to transcendence and fidelity.…”
Section: Religiosity Spirituality and Hopementioning
confidence: 99%
“…This line of reasoning is further supported by the fact that our sample consisted mostly of religious people, predominantly Roman Catholics. Catholics are encouraged to treat their work as a sacred duty, a way to serve God, and thus are expected to maintain patience, stoic perseverance, and hope (King et al 2020), even if they encounter serious obstacles on their way (see Scherer et al 2016). If this is the case, highly spiritual teachers may feel morally obliged to fulfill their duties as best as possible to please God and thus, when experiencing burnout, tend to consider quitting their job less frequently than their less spiritual peers.…”
Section: Discussionmentioning
confidence: 99%
“…This issue highlighted understudied religious socialization contexts for children and adolescents whose traditions and experiences have not typically been the focus of research, noting that there are many competing socialization contexts and phenomena that affect the religious and spiritual development of children and youth. King et al (2020) explore the link between religiousness and hope, particularly for youth living in adversity. Drawing on a relational developmental systems metatheory, this study explored how involvement in the faith-based youth-development organization, Compassion International (CI), might facilitate character strengths like hope for a youth sample in El Salvador, half of whom were involved in CI and the other half of whom were a locally matched counterfactual sample.…”
Section: Issue Overview and Contributionsmentioning
confidence: 99%